2007
DOI: 10.1103/physrevlett.98.269702
|View full text |Cite
|
Sign up to set email alerts
|

Luet al.Reply:

Abstract: Lu et al. Reply:The authors of the preceding Comment [1] argue that the patterns we measured on highly oriented pyrolytic graphite (HOPG) by electric field microscopy (EFM) [2] were a result of surface contamination (e.g., water film) and cannot be attributed to the potential fluctuations of graphite. We disagree with their arguments.The method we used is indeed suitable to measure absolute contact potential differences (CPD), and the voltage dependence shown in Fig. 1 in Ref.[2] is necessary for the calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 6 publications
5
37
0
Order By: Relevance
“…Note that the sample width changes between 1 cm and 80 µm. The OMR clearly decreases from ∼ 40% for a macroscopic sample to ∼ 20% for a still relatively large con- 2 ; the size of the domain patterns matches the results of EFM measurements [7].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Note that the sample width changes between 1 cm and 80 µm. The OMR clearly decreases from ∼ 40% for a macroscopic sample to ∼ 20% for a still relatively large con- 2 ; the size of the domain patterns matches the results of EFM measurements [7].…”
supporting
confidence: 76%
“…In fact the dielectric constant of graphite at optical frequencies is positive, insulator like (ǫ plane = 5.6 + i7.0, ǫ c = 2.25) [5,6]. Electric field microscopy [7] detects that regions of graphite are more insulating than others upon the interconnections of graphite planes produced by defects and their overall density that influences the density of states and the Fermi level. The material exhibits a huge magnetic field driven metal-insulator transition [1,8].…”
mentioning
confidence: 99%
“…40,41 As shown in Figure 3e, the surface presents several graphitic planes that show distinct electrical conductivity, in agreement with the behavior previously reported employing metal-coated AFM probes for its characterization. [40][41][42][43] We found that a single tip could be used for more than 50 hours for conductive AFM measurements without noticeable deterioration in performance (a total of > 50 images, each of a 5 µm × 5 µm area). Our transfer method brings to the fore a quick and easy approach for making these tips.…”
mentioning
confidence: 91%
“…18,[38][39][40] In bilayer systems, the interlayer coupling makes a complex structure around the band touching point. The electronic properties were theoretically studied for the band structure with or without a magnetic field, [41][42][43][44][45][46] the transport [47][48][49][50] and dynamical properties, 51) and diamagnetic susceptibility. 52) For graphene and carbon nanotubes, a continuum model suitable for a correct description of long-wavelength acoustic phonons was constructed, 53) and a similar continuum model was developed for optical phonons and the Hamiltonian for electron-phonon interactions was also derived.…”
Section: Introductionmentioning
confidence: 99%